STUDI LITERATUR POTENSI PENERAPAN INTELLIGENT BUILDING - CLIMATE ADAPTIVE BUILDING SHELL (CABS) PADA IKLIM TROPIS INDONESIA - Aldhi Nugraha Anantama (Universitas Katolik Soegijapranata, 2026)
The increasing energy consumption of buildings in tropical regions highlights the need for adaptive and climate-responsive building envelope strategies. Climate Adaptive Building Shells (CABS) have emerged as a promising approach to improving energy efficiency and indoor comfort in tropical contexts such as Indonesia. This study aims to review and synthesize existing research on CABS in Indonesia based on previous studies. The research employed a literature review of ten selected articles through a systematic process of identification, screening, and content analysis. The selected articles were subsequently coded based on the study location, building typology, physical domain, adaptation scale, research method, key findings, and research limitations before being synthesized to map the development of Climate Adaptive Building Shell (CABS) research in Indonesia. The results indicate that CABS research in Indonesia is predominantly simulation-based, with a strong emphasis on thermal and optical performance, while field validation and multi-domain integration remain limited. Despite these constraints, the reviewed studies consistently demonstrate the potential of adaptive façades to reduce cooling loads and enhance indoor environmental quality. This study highlights the need for more integrated, multi-domain, and experimentally validated research to support the practical implementation of CABS in tropical buildings.